Adherence to cognitive and physical exercise engagement: a challenge to successful dementia risk reduction and prevention efforts - O'Neil-Pirozzi, Therese M.; Cappon, Davide B.; Pascual-Leone, Alvaro (Frontiers in Dementia, 2023)
With human life expectancy and proportion of older adults increasing, global use of evidencesupported preventative methods to minimize risk of brain-related disabilities such as Alzheimer's Disease and other dementiasas well as interventions to slow rate of disease progression -is important. Sustained engagement in cognitive and physical exercise programs may prevent or delay dementia onset as well as maximize health and function of those with dementia. Despite awareness of the importance of cognitive and physical exercise to brain health, exercise program adherence by older adults is extremely challenging. In this Perspective article, we summarize what is known about contributors to exercise program adherence and strategies to promote it. We discuss our viewpoint on knowledge gaps regarding exercise adherence and research that needs to be conducted. We conclude by proposing a multi-dimensional exercise adherence assessment framework that includes portable neurophysiologic technologies to inform initial design and updating of individualized exercise programs that optimize sustained exercise program engagement and, ultimately, maximize brain health in older adults with and without mild cognitive impairment and dementia.